Factors linked to bullying in schoolchildren in Cordoba, Argentina - Cardozo, Griselda (2021)
Background: Bullying is a complex problem and research suggests focusing on adolescents’ individual characteristics, as well as exploring those contexts that affect their development, such as family and school contexts, by adopting an ecological vision. Objective: To inquire into the individual factors (prosocial/antisocial behaviors) and the characteristics of family and school contexts related to bullying behavior in adolescents attending public and private schools in the city of Córdoba. Method: A test battery was administered to 3,500 adolescents between 11 and 20 years old to measure the study variables. A multiple correspondence analysis was performed. Results: Two dimensions which explain 36.47% of data variability were observed as structural axes of the representations that identify the patterns in which the roles involved in bullying are distinguished. There is evidence that the victims share more characteristics with those not involved in bullying and the aggressors with the group called victims-aggressors, confirming that the roles in bullying are not exclusive. Conclusion: The identification of different factors constitutes a valuable input for designing the interventions aimed at prevention